Do we really know what's in our plate?. (29th March 2019) - Dourado, Miriam; Martins, Catarina; Palma, Miguel; Bettencourt-Câmara, Madalena
Abstract : Introduction: Food fraud is an ancient crime that in the last decade has received substantial attention from the criminal and food authorities, industry, academic community, media and consumers [1–5 ]. The global food fraud costs have been estimated to ascend $10 billion and $15 billion per year, affecting approximately 10% of all commercially sold food products [3 ]. In EU, food fraud crimes are considered intentional acts that violate the food law, target illicit economic gains and cause consumer deception [5 ]. Generally they do not harm the human health. This study aims to survey the reported food frauds/adulteration cases in the EU and in Portugal (PT) in the 21st century in order to identify overall patterns regarding these crimes. Materials and methods: Concerning the EU cases, we collected and analysed all food product category notifications (30) of the public Rapid Alert System for Food and Feed (RASFF) database, notified between 01.2000 and 04.2018, under the hazard category of 'fraud/adulteration' (n= 1223) [6 ], the OPSON reports (II-VI) [1 ], an Interpol-Europol project to mitigate food fraud, and the monthly summary of articles on food fraud and adulteration from the recent Knowledge Centre for Food Fraud and Quality (09.2016-04.2018)(food fraud cases n = 197) [7 ]. The PT fraud cases were retrieved and analysed from the Portuguese Economic and Food Safety Authority (ASAE)(Press release 2016-04.2018, n = 151) [8 ]. Results: 53% of the RASFF fraud notifications were carried out in 2014 and 2018. This could also reflect the recent EU efforts combating food fraud. Fish and seafood, meat, including poultry, and their products, are among the largest categories among the fraud notifications (34% of RASFF and ASAE cases; OPSON reports II-VI, 2011e2016 ≈3×10 6 tones seized), along with nuts, nuts products, and seeds and fruits and vegetables (38% of RASFF cases). 4% of the RASFF notifications concerns food presenting a serious risk and/or that required a rapid intervention. Illegal trade and/or changed expire dates are the main reasons of those alert notifications. In Portugal, fraud in wine and wine products is important (19% of ASAE cases). The predominant types of fraud described in the monthly summary articles are mislabeling and origin masking (53% and 18% of the EU cases). Fish is also a food category prone to fraud. Discussion and conclusions: In general, in EU and in PT, food categories of animal origin, namely fish, seafood, meat and their products are very vulnerable food categories to food safety frauds. Alcoholic beverages, mostly wine, extra virgin olive oil and other high quality food linked to a geographical origin, a varietal identification and/or a specific quality are very sensitive foods regarding authenticity and others deceiving consumer types of infringements.